Santiago’s Monomythic Journey in Paulo Coelho’s The Alchemist - Irfan Januar Ramadhan (LITERA KULTURA : Journal of Literary and Cultural Studies, 2020)
Hero’s journey or monomyth is a theory based on Joseph Campbell’s book The Hero with a Thousand Faces. Campbell wrote that there is a recurring pattern in myths and stories. The pattern has 3 passages, which contain 17 stages. This theory can be used to analyze Santiago’s journey in The Alchemist by Paulo Coelho as well. The finding of this research shows that most the stages of the monomyth are depicted in the novel, but some of the stages are not and the order is not exactly like what Campbell wrote in his book. This shows that the monomyth theory is not always depicted and used as a whole in literary work.